2007
DOI: 10.1111/j.1471-0307.2007.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of shredded Cheddar cheese packaged in modified atmospheres

Abstract: The microbiological quality of shredded Cheddar cheese packaged in different modified atmospheres with and without oxygen scavengers included in the packaging film was studied with the aim of determining how modified air packaging would affect the mould species present on shredded Cheddar cheese. The film with oxygen scavengers was more effective than the control film against mould growth, whereas the 73% CO2/27% N2 atmosphere resulted in the cheese with the best microbiological qualities. The three modified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…x MAP1: 0% O 2 + 0% CO 2 , MAP2: 10% O 2 + 0% CO 2 , MAP3: 0% O 2 + 75% CO 2 , MAP4: 10% O 2 + 75% CO 2. y The data reported in the table are the average sensory scores on a scale from 0 to 9 (0: not different, 9: extremely different). under MAP and air (Oyugi and Buys 2007). A decrease in lactobacilli and lactococci count during 90 days ripening of artisanal Turkish white cheese in brine has also been reported ( € Oner et al 2006).…”
Section: A-bmentioning
confidence: 75%
See 1 more Smart Citation
“…x MAP1: 0% O 2 + 0% CO 2 , MAP2: 10% O 2 + 0% CO 2 , MAP3: 0% O 2 + 75% CO 2 , MAP4: 10% O 2 + 75% CO 2. y The data reported in the table are the average sensory scores on a scale from 0 to 9 (0: not different, 9: extremely different). under MAP and air (Oyugi and Buys 2007). A decrease in lactobacilli and lactococci count during 90 days ripening of artisanal Turkish white cheese in brine has also been reported ( € Oner et al 2006).…”
Section: A-bmentioning
confidence: 75%
“…). LAB counts did not change during storage of Cheddar cheese under MAP and air (Oyugi and Buys ). A decrease in lactobacilli and lactococci count during 90 days ripening of artisanal Turkish white cheese in brine has also been reported (Öner et al .…”
Section: Discussionmentioning
confidence: 92%
“…The effects of CO 2 on the growth of lactic acid bacteria were not definite because of the microaerophilic nature of these bacteria, and they can grow under the CO 2 atmosphere. Oyugi and Buys (2007) reported that under the CO 2 packaging conditions, the lactic acid bacteria in shredded Cheddar cheese can be inhibited slightly. Eliot et al.…”
Section: Resultsmentioning
confidence: 99%
“…F. solani was specifically detected in the products coming from Ollomont cellar whereas it was absent from the Pré‐Saint‐Didier ones. This mould is not commonly related to dairy environment but it has been recently described in a paper regarding Cheddar cheese packaging (Oyugi and Buys 2007).…”
Section: Discussionmentioning
confidence: 99%